Research on the impact of FDI and environmental regulation on the industrial structure upgrading in the Yellow River Basin - Yu, Jinxiu (Frontiers in Earth Science, 2024)
Since the reform and opening up, the inflow of foreign direct investment (FDI) has provided a steady stream of capital, technology, talent and other resources for the development of the Yellow River basin, while caused problems such as environmental pollution, ecological fragility and industrial structure upgrading difficulties to some extent. Environmental regulation is a pivotal initiative to achieve mutual harmony between ecological environment and economic development, which could enhance the quality of the introduction of FDI and accelerate the green transformation of the development mode. Therefore, based on urban panel data from 2006-2019, this study empirically examined the impact of FDI and environmental regulation on industrial structure upgrading in the Yellow River Basin. Moreover, taking environmental regulation as a threshold variable, a panel threshold model was established to further explore the role of environmental regulation in the impact of FDI on industrial structure upgrading in the Yellow River Basin. The empirical results indicated that: (1) The relationship between FDI and industrial structure upgrading in the Yellow River Basin is not a simple linear relationship, but an inverted “U”-shaped relationship that rises first and then falls, and the results of this inverted “U”-shaped relationship are still robust after replacing key indicators. (2) The environmental regulation policy has a driving effect on the upgrading of industrial structure in the Yellow River Basin. (3) Environmental regulation has a positive role in the influence of FDI on the industrial structure upgrading in the Yellow River basin, and the positive role increases gradually as the intensity of environmental regulation increases moderately, but if the intensity of environmental regulation is too high, it will have a negative impact on the upgrading of industrial structure in the Yellow River basin to some extent. In the future, policy-makers should make reasonable and effective use of FDI and improve the quality of FDI; reasonably formulate environmental regulation policies; coordinate the intensity of FDI and environmental regulation; thus, bring into play the promotion effect of FDI and environmental regulation on industrial structure upgrading, and then realize the win-win of ecological protection and high-quality economic development in the Yellow River Basin.